DASAR KUALIFIKASI CURI PATOLOGIS (KLEPTOMANIA) DI DALAM PERTANGGUNGJAWABAN PIDANA - Sinta Paramita Sari, Anak Agung Ayu; Atmadja, I Dewa Gede (Kertha Wicara : Journal Ilmu Hukum, 2013)
Stealing is a criminal perpetration based in article 362 Indonesian Criminal Code. Besides a criminal perpetration in the Indonesian Criminal Code also arrange about negative form of criminal liability. In article 44 Indonesian Criminal Code arrange the people with ill conditions cannot be responsible for criminal perpetration he did in whole or in partially. Cannot be responsible for partially of one of them applies to people with kleptomania. In the Indonesian Criminal Code not explained about the conditions of people who are not able to be responsible in whole or in partially, and the basis used in determining the liability of people who have qualified psychiatric disorders such as kleptomania. This paper aims to explain the basis of the criminal law to see accountability people with kleptomania.
Keywords: Kleptomania, Pathological Steal, Criminal Responsibility.